Joaquín Casalduero, Forma y visión de "El diablo mundo" de Espronceda. Ínsula, Madrid, 1951; 153 pp. - Levy, Denah (El Colegio de México, 1954)
Se reseñó el libro: Forma y visión de "El diablo mundo" de Espronceda.